5 - Higher Education in Ethiopia: The Vision and Its Challenges: William Saint - William Saint (Journal of Higher Education in Africa, 2004)
Ethiopia is embarked on a higher education expansion and reform programme of impressive dimensions. Expansion will create new universities, establish three sys- tem support agencies, mount new courses, and triple enrolments. Reforms intro- duce increased institutional autonomy, curriculum revisions, new funding arrange- ments and student contributions by means of a graduate tax. This article analyses current higher education reform efforts in Ethiopia. It begins by sketching the so- cial context in which higher education is situated and describing the country’s higher education system. An assessment of tertiary education financing follows. Management capacities and efficiency in the use of these resources are then dis- cussed, noting the particular challenges posed by HIV/AIDS. Educational quality and relevance are subsequently addressed. Analysis points out potential weaknesses in the reform programme but concludes that enrolment expansion targets are likely to be met. However, the dynamics of expansion may well generate difficulties in maintaining educational quality.